Order Estimates for the Kolmogorov Widths of Weighted Sobolev Classes with Restrictions on Derivatives - Vasil’eva, Anastasia (Eurasian Mathematical Journal, 2020)
In this paper order estimates for the Kolmogorov widths of weighted Sobolev classes with restrictions on the derivatives of order r and 0 are obtained. The functions are defined on a John domain or on Rd.